Developing a Molecularly Imprinted Electrochemical Sensor for Selective Detection of Roxithromycin from Food Samples via Green Synthesis - Budak, Fatma; Cetinkaya, Ahmet; Uzunoglu, Aytekin; Ozkan, Sibel A. (Springer, 2025)
Roxithromycin (ROX), a broad-spectrum macrolide antibiotic, is derived from erythromycin (Markham et al.). ROX is mainly used to treat infections in humans and animals and is easily found and accumulated in the natural environment (Jiang et al. 2021). The sensor for quantitative analysis of ROX was developed via electro-polymerization (EP) on a glassy carbon electrode (GCE) using alginate (ALG), chitosan (CHIT), and titanium IV oxide nanoparticles (TiO2NPs), and it offers a green process. The ROX/TiO2NPs/ALG/CHIT@MIP/GCE sensor has exhibited excellent efficiency and stability for ROX. Differential pulse voltammetry (DPV) was used as the electrochemical analysis method in the developed sensor. Additionally, both surface morphology (scanning electron microscopy (SEM) and X-ray Photoelectron Spectrometry (XPS)) and electrochemical (electrochemical impedance spectroscopy (EIS), cyclic voltammetry (CV)) characterizations of the ROX/TiO2NPs/ALG/CHIT@MIP/GCE sensor were performed. Under the optimal conditions, the sensor calibration range was found to be 1 x 10-13 M to 1 x 10-12 M, with a very low limit of detection (LOD). With the designed sensor, ROX analysis of food samples and satisfactory recovery results were obtained, demonstrating the sensor's accuracy. Moreover, the effects of different interfering agents in milk and fruit juice samples on the ROX peak current were investigated to evaluate the selectivity of the designed sensor. The designed sensor demonstrated highly sensitive, reliable, repeatable, stable, and, most importantly, selective properties for ROX. Finally, four different green metric calculation methods were used to determine the study's green profile score.
Keywords: Roxithromycin; Electrochemical sensor; Food samples; Molecularly imprinted polymer